SWEAR WORDS IN BAD BOYS II: A SEMANTIC ANALYSIS - Kristiano, Johan Tobias; Ardi, Priyatno (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
English movies have become a medium for the global spread of English swear words. However, not all people from non-English speaking countries know and understand the literal meanings of these words. This qualitative research aims to figure out the semantic referents of swear words in the film Bad Boys II. Content analysis was employed as its method. The results of this study show that nine semantic referents of swear words were used in the movie, namely sexual references, profane or blasphemous, scatological and disgusting objects, animal names, ethnic-racial-gender slurs, psychological-physical-social deviations, ancestral allusions, substandard vulgar terms, and offensive slang. Thus, Bad Boys II has a vast variety of swear words.DOI: doi.org/10.24071/llt.2018.210208